The Influence of Service Quality and Brand Image on Purchase Decisions: Study on Consumers of Muslim Fashion Products in Bandung City - Nadya Dwi Andini; Imelda Megawati (Majalah Bisnis & IPTEK, 2023)
Researchers in Bandung did a study to examine the influence of service quality and brand image on consumer decision-making in purchasing Muslim fashion products. In addition, the research aimed to determine the dominant component, either service quality or brand image, that had the most impact on the purchasing choices of a sample of 100 consumers involved in the study by completing a questionnaire. By employing path analysis, this study substantiated the legitimacy of service quality and brand image factors among customers of Muslim fashion products in Bandung City. Therefore, the results underscore the significance of improving service quality and enhancing brand image to influence purchasing decisions. The findings of the study indicate a substantial relationship between Service Quality (X1) and Purchasing Decisions (Y), as well as between Brand Image (X2) and Purchasing Decisions (Y). Judging from the results of research on Service Quality (X1) on Purchase Decisions (Y) for consumers of Muslim fashion products in the city of Bandung, to increase purchasing decisions, companies should be able to improve service quality by providing training on how to be responsive and reliable customer service so they can perform better service than before. Judging from the research results on the effect of brand image (X2) on purchasing decisions (Y) for Muslim fashion products in Bandung, companies need to build good brand name awareness to improve purchasing decisions. Because it is an effort to form a brand approach to consumers or their target market, this can work through collaboration with Influencers on social media to use products from one of the Muslim fashion products that aim to influence their followers indirectly. In addition, it is necessary to sponsor several events relevant to the same target audience.